МАТЕМАТИЧНЕ МОДЕЛЮВАННЯ ПЕРІОДИЧНИХ ПРОЦЕСІВ В НЕЛІНІЙНИХ ЕЛЕКТРОМАГНІТНИХ КОЛАХ - Добушовська , І.А. (Інститут електродинаміки НАН України, Київ, 2014)
The problem of calculating the stationary modes in nonlinear electrical circuits with reactive elements that are under periodic disturbances is considered. The problem is solved as a boundary value problem for a system of differential equations with periodic boundary conditions, which describe the dynamic steady state that can have obtained dependencies of state variables on the period without resorting to solving the problem in the time domain. Presentation in algebraic form system of differential equations is performed using projection method of spline approximation. The resulting system of nonlinear algebraic equations is solved by the method of continuation parameter that allows investigating the influence on the nature of periodic dependencies of coordinates as value of a periodic disturbances, and any other parameter of electric circuit. References 4, figure 2.